1995
DOI: 10.1063/1.114796
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman spectroscopy of the Fe3+ center in GaN

Abstract: We report an optical investigation of the Zeeman behavior of the deep iron acceptor in GaN grown on 6H–SiC. The characteristic ground state splitting of the near-infrared luminescence transition at 1.2988 eV allows for an unambiguous assignment to Fe3+previously proposed on the basis of ODMR results. The observed luminescence lifetime of 8 ms as well as the fine structure of the excited state are consistent with a 4T1(G)–6A1(S) transition. The 4T1(G) state is found to couple only weakly to ε-type phonon modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…[5]. By means of optically detected magnetic resonance [6] this PL peak could be related to an electron spin resonance signal which exhibited the symmetry properties expected for Fe 3+ on substitutional Ga sites in hexagonal GaN [6][7][8]. From PL excitation spectroscopy studies it was suggested that the deep acceptor level Fe 3+/2+ is located 2.5-2.6 eV above the valence band edge E V [6,9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5]. By means of optically detected magnetic resonance [6] this PL peak could be related to an electron spin resonance signal which exhibited the symmetry properties expected for Fe 3+ on substitutional Ga sites in hexagonal GaN [6][7][8]. From PL excitation spectroscopy studies it was suggested that the deep acceptor level Fe 3+/2+ is located 2.5-2.6 eV above the valence band edge E V [6,9,10].…”
mentioning
confidence: 99%
“…To date, Fe has been found to be a frequent contaminant in GaN thin films grown by metal organic vapor phase epitaxy (MOVPE), hydride vapor phase epitaxy (HVPE) [9,12], and by the sublimation sandwich method with typical Fe concentrations around 10 17 -10 18 cm −3 [7,8]. On the other hand, attempts to intentionally produce Fe deep centers by doping during growth or by means of ion implantation have not been very successful [3,13,14].…”
mentioning
confidence: 99%
“…It was observed that all A, B, C, and D lines split into several components. The obtained spectra are much better defined than the magnetoluminescence data reported (only for A line) for GaN:Fe layers grown on sapphire [7]. For each line different splitting was found.…”
Section: Resultsmentioning
confidence: 53%
“…The full width at half maximum (FWHM) of the ZPL scales with the Fe concentration between 120 and 270 µeV, proving the samples to be of better quality than those studied previously [7]. This is mainly regarding the strain free incorporation of Fe on Ga site and was confirmed by electron paramagnetic resonance (EPR) experiments.…”
Section: Figure 1 Presents Pl Spectra Of the Internal Fementioning
confidence: 67%
“…center in GaN exhibits a structured near infra red (IR) luminescence at 1.299 eV with a 8 ms lifetime [6,7]. By means of photoluminescence excitation (PLE) Heitz et al identified higher excited states,…”
Section: Introductionmentioning
confidence: 99%